(untitled) (BIRDEM Medical Journal, 2017)
Background: Hepatitis B (HBV) and hepatitis C virus (HCV) infection is common among patients on maintenance hemodialysis (MHD). This study was undertaken to observe prevalence of hepatitis B and C infection in hemodialysis patients, their family members and dialysis staffs. Methods: In this cross-sectional study 3 groups were included as gr-1 patients on MHD, the first-degree relatives in gr-2 and the dialysis staffs as gr-3. Clinical and laboratory investigations were done. Viral serology included hepatitis B surface antigen (HBsAg) and antibody against hepatitis C virus (anti-HCV) done by enzyme linked immunosorbent sorbent assay (ELISA) method. Results: Total 150 subjects were analyzed where 50 were in gr-1, 60 gr-2 and 40 in gr-3. In gr-1 MHD patients, HBV infection was positive in 12% and HCV in 71%. None of the viral markers were positive in family members and dialysis staffs. Blood transfusion (BT) was taken by 76% MHD patents. The frequency of HBV and HCV infection was of similar pattern in both BT dependent and non BT group (P=NS).When HCV positive and negative patents were (71 vs. 29%, p<0.001) compared, dialysis duration (37 ± 34 vs. 11± 6 months, p<0.001) was found higher in positive patients. Conclusion: This survey on dialysis patients showed that prevalence of hepatitis B and C virus infections was higher in Bangladeshi patients on MHD groups. Horizontal spread of these viruses is negligible in caregivers and dialysis staffs. Birdem Med J 2018; 8(1): 42-46